2019
DOI: 10.3389/fmicb.2019.00867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin Rich Onion Extracts on Bacterial Quorum Sensing

Abstract: Quorum sensing (QS) regulates bacterial gene expression and studies suggest quercetin, a flavonol found in onion, as a QS inhibitor. There are no studies showing the anti-QS activity of plants containing quercetin in its native glycosylated forms. This study aimed to evaluate the antimicrobial and anti-QS potential of organic extracts of onion varieties and its representative phenolic compounds quercetin aglycone and quercetin 3-β-D-glucoside in the QS model bacteria Chromobacterium violaceum ATCC 12472, Pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 59 publications
4
62
0
3
Order By: Relevance
“…61 A significant reduction in lecithinase production was observed only with 1/4x and 1/8x MIC of EDTA. These findings were similar to what was reported by previous studies on other compounds such as that conducted by Mattmann and Blackwell about furanone C-30, 62 Musthafa et al about phenylacetic acid, 63 Quecan et al about onion extract 58 and Ahmed et al about cinnamaldehyde and salicylic acid. 64 Motility is an important factor in both adhesion and biofilm formation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…61 A significant reduction in lecithinase production was observed only with 1/4x and 1/8x MIC of EDTA. These findings were similar to what was reported by previous studies on other compounds such as that conducted by Mattmann and Blackwell about furanone C-30, 62 Musthafa et al about phenylacetic acid, 63 Quecan et al about onion extract 58 and Ahmed et al about cinnamaldehyde and salicylic acid. 64 Motility is an important factor in both adhesion and biofilm formation.…”
Section: Discussionsupporting
confidence: 92%
“…24,26 Also, Aboelenin et al, 2017 reported a similar effect of sub-MICs of EDTA on the viability of E. coli. 51 Many studies reported that several antibacterial agents (tobramycin, 52 ciprofloxacin, 53 azithromycin, 54 ceftazidime, 48 aminoglycosides, tetracyclines 55 and piperacillin-tazobactam 56 ), natural plant-derived compounds as gall extract 2,57 and onion extract 58 and drugs such as aspirin 37 can decrease QS signals (HSL) in P. aeruginosa at sub-MICs without any bactericidal effect. Our study showed the same result whereas both tyrosol and EDTA at sub-MICs verified a significant reduction of C4-HSL and C12-HSL signal molecules production in P. aeruginosa PAO1.…”
Section: Discussionmentioning
confidence: 99%
“…They established that 4 -Qmg treatment prevented the production of virulence factors (violacein, elastase, and pyocyanin) and biofilm formation in the test pathogens by antagonizing the virulence factor regulator (Vfr) and QS signal receptor (LasR) [129]. Another recent study witnessed the anti-QS activity of quercetin aglycone and 3-Qmg from onion on C. violaceum, P. aeruginosa, and Serratia marcescens by inhibiting violacein production and swarming ability [130]. The above discussion imparts that the use of Allium-derived flavonols could be a sustainable solution to mitigate issues relating to the resistant microbial infections.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…In a placebo-controlled double-blind parallel-group comparison study for subjects with body mass index (BMI) of ≥25 kg/m 2 , daily intake of tea containing 110 mg quercetin glycoside for 12 weeks significantly decreased visceral fat area (VFA) at weeks 8 and 12 after intake compared to that in the placebo food intake group [10]. The mechanism underlying suppression of fat accumulation by quercetin was indicated to involve suppression of the expression of peroxisome proliferator-activated receptor γ which is related to fat accumulation, and sterol regulatory element-binding protein 1 and fatty acid synthase which are related to fatty acid synthesis, and to increase the expression of cAMP which is related to lipolysis [11][12][13].Onion is the one of the most popular vegetables in the world, and a major source of quercetin (28.4-48.6 mg/100 g) [14]. In the current clinical trial, we used the two quercetin-rich onion cultivars 'Quergold' and 'Sarasara-gold' to adjust the amount of quercetin contained in the test food.…”
mentioning
confidence: 99%
“…Onion is the one of the most popular vegetables in the world, and a major source of quercetin (28.4-48.6 mg/100 g) [14]. In the current clinical trial, we used the two quercetin-rich onion cultivars 'Quergold' and 'Sarasara-gold' to adjust the amount of quercetin contained in the test food.…”
mentioning
confidence: 99%